Clinical Significance of Prehospital Telecommunication Defined as the Critical Stroke Call Pathway in Acute Ischemic Stroke Requiring Intra-Arterial Recanalization Therapy - Lee, H.; Kim, S.H.; Baek, J.W.; Jin, S.-C. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: To reduce the door-to-puncture time, which is a prognostic factor for the clinical outcome after intra-arterial recanalization therapy, we established a prehospital telecommunication strategy between neurointerventionalists and emergency medical technicians, namely, the critical stroke call pathway. We retrospectively evaluated the clinical significance of the critical stroke call pathway by comparing the door-to-puncture time and clinical outcome of the critical stroke call pathway with those of the routine stroke pathway.MATERIALS AND METHODS: From January 2018 to June 2020, one hundred seventy-one patients with anterior circulation occlusion who underwent arterial recanalization therapy via the emergency department were included in this study. Patients were divided into the critical stroke call pathway group (n = 75, 43.9%) and the routine stroke pathway group (n = 96, 56.1%).RESULTS: The critical stroke call pathway group exhibited a shorter door-to-puncture time than the routine stroke pathway group (median, 87 minutes; interquartile range, 63–107 minutes; P < .001). On multivariable analysis, a good clinical outcome (3-month mRS, 0–2) was independently associated with a shorter door-to-puncture time (adjusted OR, 0.998; adjusted 95% CI, 0.996–1.000; P = .027). In patients with an NIHSS score on admission of ≤11, an excellent clinical outcome (3-month mRS, 0–1) was more frequently achieved in the critical stroke call pathway group than in the routine stroke pathway group (22/33, 66.7%, versus 21/48, 43.8%; P = .042).CONCLUSIONS: In our study, compared with the routine stroke pathway, the critical stroke call pathway remarkably reduced the door-to-puncture time for arterial recanalization therapy, with better clinical outcomes, especially in patients with a relatively good clinical status.CSCPcritical stroke call pathwayEMTemergency medical technicianIATintra-arterial recanalization therapyIQRinterquartile rangeRSProutine stroke pathway